Enhancing Publication Quality as a Key to Outstanding Lecturer Performance - Anwar Wahid; Mclean HY; Cita St.Munthakhabah R; Laode Muh. Zulfardin Syah; Zam’ah (Information Technology Education Journal, 2025)
This study examines the crucial relationship between the quality of scientific publications and lecturer performance in higher education institutions. As a primary indicator of academic achievement and professional development, enhancing publication quality is a vital factor in fostering the superior teaching and research capabilities of lecturers. This article describes the implementation and evaluation of a national webinar titled “Enhancing Scientific Publication Quality Toward Outstanding Lecturer Performance,” organized by the Information Technology Education Study Program at the University of West Sulawesi. This webinar aimed to improve lecturers' competence in writing and publishing high-quality scientific articles that meet the standards of reputable national and international journals. The event was conducted online via the Zoom Meeting platform on August 7, 2025, featuring an experienced keynote speaker. A total of 118 participants registered and completed the event. The evaluation was conducted through an online form, covering satisfaction with the material, the speaker's delivery, and the relevance of the content to the participants' academic needs. The findings of this study identify key strategies for improving publication quality—such as targeted training, mentorship programs, and a collaborative research environment—which significantly contribute to enhancing lecturer performance. This study concludes that strengthening publication quality is not only a path to academic excellence but also an essential component in developing competent and effective lecturers, which in turn enhances institutional reputation and student learning outcomes. Recommendations for policymakers and educational institutions are also discussed to support the continuous professional development of lecturers.